2022
DOI: 10.1186/s13011-022-00435-9
|View full text |Cite
|
Sign up to set email alerts
|

Youth substance use service provider’s perspectives on use and service access in ontario: time to reframe the discourse

Abstract: Background Age is a critical factor in substance use and related outcomes, with adolescence being a particularly sensitive period. Early initiation of substance use has been linked with higher risk for developing substance use disorders. In Ontario, Canada, substance use is common among youth, yet treatment is underutilized, suggesting the potential for an unmet need in terms of substance use care. Despite these challenges, there is limited research examining factors that contribute to youth su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Studies have shown that a difficult relationship with family members (Temple et al, 2022), a poor relationship with parents and a lack of parental monitoring and family support (Ali et al, 2022) are predictors of an increased use of illicit substances (alcohol, cigarettes, and drugs) among youths.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that a difficult relationship with family members (Temple et al, 2022), a poor relationship with parents and a lack of parental monitoring and family support (Ali et al, 2022) are predictors of an increased use of illicit substances (alcohol, cigarettes, and drugs) among youths.…”
Section: Introductionmentioning
confidence: 99%
“…Although the level of education cannot be increased, attempts may be made at the start of the therapy to at least educate the person with substance abuse about the negative effects of substance abuse and effectiveness of CBT to counter them. An earlier qualitative study [ 27 ] showed that young adults who were not educated about the potential adverse effects of addictive substances were more inclined to abuse substances. Educational reforms were suggested in this study [ 27 ] for the awareness of youth about the risks of substance use for physical health and psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier qualitative study [ 27 ] showed that young adults who were not educated about the potential adverse effects of addictive substances were more inclined to abuse substances. Educational reforms were suggested in this study [ 27 ] for the awareness of youth about the risks of substance use for physical health and psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
“…This trend is also reflected in surveys conducted in Canadian universities, as a previous survey, with more than 23,000 Canadian university students, found that prior to legalization, students who self-reported using cannabis (i.e., from daily use to less than once a year) ranged from 23.4% to 56.4% in 49 universities across Canada (Brownell, 2018). Research has also found that the ongoing discourse regarding legalization of cannabis has led to the normalization of cannabis consumption, with increased numbers of youth experimenting with cannabis, despite cannabis remaining illegal for them (Ali et al, 2022).…”
Section: Cultural and Contextual Differences About Drug Use Between C...mentioning
confidence: 99%
“…These factors help drive a strong market demand for cannabis. Culturally, cannabis use has also been normalized in Canada (Ali et al, 2022). Some researchers suggested that cannabis attaches to the cultural hierarchy and reflects this ‘white’, ‘male’, and ‘middle-class’ dominant culture (Mabee, 2019; Schlussel, 2017).…”
Section: Theoretical Lensmentioning
confidence: 99%